Diversifikasi Olahan Produk Pisang sebagai Potensi Desa Putrapinggan Kecamatan Kalipucang Kabupaten Pangandaran - Noneng Masitoh; Yuyun Yuniasih; Mira Rahmawati; Wilman Marino (Indonesian Journal of Community Services, 2022)
Putrapinggan Village is a village that is included in the Pangandaran Regency area with abundant natural resources, one of its mainstay commodities is processed banana products in the form of banana chips and sales. The potential of processed banana products has not been optimally absorbed because it is only produced based on the request of the packaging center without being able to independently expand the market. The purpose of community service is to increase knowledge and skills regarding the diversification of processed banana products so that people know how to modify the product so that it is more diverse, able to last a long time, and provides added value. Methods in implementing this community service program include socialization of activities; Problem mapping; Organizing training by involving residents who use processed bananas; and Community assistance in the form of making banana processed products. The results of the service activities have achieved the goal of increasing insight into the diversification of banana processing and improving skills in making various banana products for higher selling values, including banana cakes, banana steamed cakes, banana cakes, and banana satay.